Lexical and Grammatical Meanings in Solopos Newspaper Headlines July—September 2024 Edition - Saiful Mukminin, Muhamad; Dui Putra, Libra (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The lexical and grammatical meanings in newspaper headlines play an important role in ensuring the accuracy of information, attracting readers' attention, and building narratives. The present research aims to analyze the lexical and grammatical meanings in the headlines of Solopos newspaper editions from July to September 2024. The approach used in the present research is qualitative descriptive, with data taken from 77 headlines of the newspaper. Data collection techniques are conducted through observation and note-taking, while data analysis is performed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results of the research indicate that the lexical meanings in the headlines are identified into the word classes of nouns, verbs, and adjectives. Additionally, grammatical meanings are found in the forms of affixation, reduplication, composition, conversion, abbreviations, and acronyms. The conclusion of the present research is that the lexical and grammatical meanings in the headlines of Solopos newspaper editions from July to September 2024 are generally quite appropriate, although there are several words that have the potential to cause misinterpretation